(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Sulfuric acid and a Compounds of cobalt, nickel, copper, cadmium, and iron have been created by combining a Schiff base obtained from 2-amino-5-(2-amino-1,3,4-thiadiazolyl)-1,3,4-thiadiazole (1). The ligand and its complexes have been analyzed using techniques such as infrared and 1H nuclear magnetic resonance spectra, elemental investigations, The techniques used include ultraviolet-visible spectroscopy and discrepancy current investigation using thermogravimetry (TGA-DTA). Analytical data shows that the metal-to-ligand proportion in Cu (II) complexes is 2:2, but in Co (II), Ni(II), Cd(II), and Fe(II) complexes, it is 1:2. N- [5’ -Amino-2,2’ -bis(1,3,4-thiadiazole)-5-yl] is the chemical name of the substance. With the exception of Ni (II) and Cu (II), the predicted structures for the formation of Fe (II), Co (II), and Cd (II) are octahedral, tetrahedral, and square-planar features, respectively. The synthesis of novel Two distinct ligands, Benzaldehyde with two carbon and hydrogen bonds Cobalt (II), nickel (II), copper (II), and zinc (II) were among the metallic compounds reacted with Benzaldehyde picolinoyl hydrazine (CBPH) and 4-methylbenzoylhydrazone (CBMH) are two examples. This reaction led to the formation of metal complexes. Condensation reactions using Hydrazide, 2-carboxy benzaldehyde, 4-methylbenzoyl, and picolinoyl estersindividually, were used to produce CBMH and CBPH. [M(L-H)2] complexes are genuine. The characterization of xH2O was performed using spectral measurements, including UV-Vis, IR, molar conductance, and chemical analysis. All the complexes involving the hydrazones CBMH and CBPH have the ligand function, exhibiting monobasic tridentate characteristics.